Combining ability in the function of inbreeding for yield and average fruit weight in Cucurbita moschata Duch. ex Poir. - Restrepo-Salazar, Javier Alonso; Vallejo-Cabrera, Franco Alirio; Restrepo-Salazar, Edwin Fernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
In order to estimate the general and specific combining ability (GCA and SCA) in the function of inbreeding, three diallel crossings of butternut squash C. moschata Duch. ex Poir. were evaluated, each coming from six parents with three levels of inbreeding (S0, S1, S2). A two-stage nested design was used with four replicates. Yield per plant (YPP) and average fruit weight (AFW) were analyzed. In the So generation, only the GCA effects were important in the expression of YPP and AFW. In the first generation of inbreeding (S1), both the GCA and SCA effects were important in the genetic control of YPP and AFW. In the second generation of inbreeding (S2), both the GCA and SCA effects were again significant in the expression of AFW. The UNAPAL-Dorado (S0 parent) and UNAPAL-Abanico-75-1 × UNAPAL-Llanogrande-2 (hybrid of S2 inbred lines) are the most indicated genotypes for improving the AFW with intra-population recurrent and reciprocal recurrent selection, respectively, with the target market of fresh consumption by consumers who prefer to buy whole fruits and not sliced fruits. Similarly, the recommended genotypes for improving the AFW for the fresh consumption market and for agro-industrial use by consumers, for whom the weight of the fruit is not a limiting trait for acquisition, include UNAPAL-Abanico- 75-2 (S2 inbred line) with intra-population recurrent selection, UNAPAL-Abanico-75-1 × UNAPAL-Llanogrande- 1 (hybrid of S1 inbred lines) and UNAPAL-Abanico-75-1 × UNAPAL-Dorado (hybrid of S2 inbred lines), both with reciprocal recurrent selection.